2023
DOI: 10.3389/fphar.2023.1190967
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Remarkable response to sintilimab, lenvatinib, and nab-paclitaxel in postoperative metastatic chemotherapy-resistant combined hepatocellular-cholangiocarcinoma

Nan Zhou,
Chuan-Fen Lei,
Si-Rui Tan
et al.

Abstract: Background: Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a highly aggressive malignancy with a poor prognosis. However, there are no consensus treatment guidelines, and decisions are usually extrapolated from intrahepatic cholangiocarcinoma (ICC) or hepatocellular carcinoma (HCC). Given that cHCC-CCA owns the unequivocal presence of both hepatocytic and cholangiocytic differentiation, a combination regimen of anti-PD1 antibody, multikinase inhibitor, and chemotherapy targeting against both componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Recently, a retrospective, multicenter cohort study reported an overall response rate of 29% with immune checkpoint inhibitors in patients with cHCC-CC[ 53 ]. Recently published studies on the role of immunotherapy have been discussed in Table 3 [ 52 - 60 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, a retrospective, multicenter cohort study reported an overall response rate of 29% with immune checkpoint inhibitors in patients with cHCC-CC[ 53 ]. Recently published studies on the role of immunotherapy have been discussed in Table 3 [ 52 - 60 ].…”
Section: Treatmentmentioning
confidence: 99%